2018
DOI: 10.5847/wjem.j.1920-8642.2018.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an educational intervention on medical records documentation

Abstract: BACKGROUND: Inaccurate and incomplete documentation can lead to poor treatment and medicolegal consequences. Studies indicate that teaching programs in this fi eld can improve the documentation of medical records. The study aimed to evaluate the effect of an educational workshop on medical record documentation by emergency medicine residents in the emergency department. METHODS: An interventional study was performed on 30 residents in their fi rst year of training emergency medicine (PGY1), in three tertiary r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 8 publications
0
18
1
1
Order By: Relevance
“…There is some evidence that educational and training programs and feedback are effective in improving medical record documentation by healthcare providers. 27 Updating or redesigning record forms can also help to improve documentation. 27,28 Medical records are important for both identifying at-risk patients and for service-level reporting and analysis, and it is therefore important for healthcare services to maintain accurate and up-to-date records.…”
Section: Implications For Public Health Practicementioning
confidence: 99%
See 2 more Smart Citations
“…There is some evidence that educational and training programs and feedback are effective in improving medical record documentation by healthcare providers. 27 Updating or redesigning record forms can also help to improve documentation. 27,28 Medical records are important for both identifying at-risk patients and for service-level reporting and analysis, and it is therefore important for healthcare services to maintain accurate and up-to-date records.…”
Section: Implications For Public Health Practicementioning
confidence: 99%
“…27 Updating or redesigning record forms can also help to improve documentation. 27,28 Medical records are important for both identifying at-risk patients and for service-level reporting and analysis, and it is therefore important for healthcare services to maintain accurate and up-to-date records. The failure to document risk status is also a potential barrier to continuity and coordination of care, especially in services with high staff turnover.…”
Section: Implications For Public Health Practicementioning
confidence: 99%
See 1 more Smart Citation
“…The research carried out on resident doctors reported an increase in the quality of medical record documents after training activities/workshops. [20][21][22] A similar study in an Ethiopian hospital stated that the presence of training interventions significantly increased the completeness of filling in medical records. 23 Dewi and Agustina stated that medical officers' compliance, such as those in charge, is lacking due to their business.…”
Section: Resultsmentioning
confidence: 99%
“…It is demonstrated by evidence that educational interventions can significantly improve documentation quality among doctors. [ 25 ] Some interviewees claim performing clinical work and documentation by nurses has reduced the effectiveness of documentation. The need for trained employees in the field of documentation and its impact, on the other hand, should be taken into account.…”
Section: Discussionmentioning
confidence: 99%